SIMULATION AND OPTIMIZATION OF THE SERVICE AND DELIVERY PROCESS IN PHARMACY - Tavares, Wagner Cesar Maria; Herculani, Rhadler (Revista Interface Tecnológica, 2020)
A good customer service and quality services provided is essential for the development and success of any organization, thinking about it, the objective of this article is to suggest the optimization in the service and delivery of medicines in a pharmacy in the interior of São Paulo. For this, the support of a software called ARENA was obtained, which through it simulated the activities of attendance, sales, separation and delivery of medication orders in order to optimize the delivery processes. Thus, computer simulations were performed in ARENA, showing good results both in the use of employees and in customer service. Through the analyzes presented, it is concluded that the pharmacy has a good planning in the design of its delivery processes.